Two new species of Gyrodactylus von Nordmann, 1832 (Monogenoidea: Gyrodactylidae) parasitizing introduced poeciliids in Patagonia - Vega, Rocio; Razzolini, Emanuel; Arbetman, Marina; Viozzi, Gustavo (Zootaxa, 2019)
Gyrodactylus superbus (Szidat, 1973) Popazoglo & Boeger, 2000 was described from Corydoras paleatus (Jenyns) (Callichthyidae) and represents the only known viviparous gyrodactylid reported from the Parano-Platense basin of Argentina. We describe two new species of viviparous neotropical gyrodactylids parasitizing the introduced poeciliid, Cnesterodon decemmaculatus (Jenyns, 1842) (Poeciliidae), from southern Argentina: Gyrodactylus decemmaculati n. sp. and Gyrodactylus breviradix n. sp. The new species differ from other gyrodactylids parasitizing poeciliids in the morphology of superficial bars and hooklets. Gyrodactylus decemmaculati n. sp. has a superficial bar with two robust and rounded anterolateral projections (each with a ventral lobe), and a subtriangular shield, and has a slender hooklet with a delicate recurved point, a straight, elongate shaft, and a depressed, acute toe. Gyrodactylus breviradix n. sp. has a superficial bar with two robust, elongate anterolateral projections, folded inward, and a trapezoidal shield, and has a hooklet with a short point, angled at 90º, ending before level of toe tip, a straight, short shaft, a round, prominent heel, and a pointed, depressed toe. These identifications were supported by DNA analyses based on sequences of the ITS2 region and a barcoding gap analysis. Sequences of the Cytochrome oxidase II gene and fragments of the Internal Transcribed Spacers 1 for both species are also provided.